Quantum phase transitions between a class of symmetry protected topological states - Tsui, Lokman; Jiang, Hong-Chen; Lu, Yuan-Ming; Lee, Dung-Hai (Nuclear physics. B, 2015)
The subject of this paper is the phase transition between symmetry protected topological states (SPTs). We consider spatial dimension d and symmetry group G so that the cohomology group, Hd+1(G,U(1)), contains at least one Z2n or Z factor. We show that the phase transition between the trivial SPT and the root states that generate the Z2n or Z groups can be induced on the boundary of a (d+1)-dimensional G×Z2T-symmetric SPT by a Z2T symmetry breaking field. Moreover we show these boundary phase transitions can be “transplanted” to d dimensions and realized in lattice models as a function of a tuning parameter. The price one pays is for the critical value of the tuning parameter there is an extra non-local (duality-like) symmetry. In the case where the phase transition is continuous, our theory predicts the presence of unusual (sometimes fractionalized) excitations corresponding to delocalized boundary excitations of the non-trivial SPT on one side of the transition. This theory also predicts other phase transition scenarios including first order transition and transition via an intermediate symmetry breaking phase. •We study the phase transitions between symmetry protected topological states.•We provide a holographic interpretation.•We engineer simple lattice models.